Predictors of linear accelerator versus Gamma Knife stereotactic radiosurgery use for brain metastases in the United States - McClelland III, Shearwood (J Radiosurg SBRT, 2020)
INTRODUCTION: Stereotactic radiosurgery (SRS) for brain metastases is predominantly delivered via single-fraction Gamma Knife SRS (GKRS) or linear accelerator (LINAC) in up to five fractions. Predictors of SRS modality have been sparsely examined on a nationwide level. METHODS: An observational cohort study was performed on patients receiving SRS for brain metastases from non-small cell lung cancer from 2010 to 2016 at Commission on Cancer-accredited hospitals throughout the United States (US). A multivariable logistic regression model characterized SRS receipt, adjusting for patient age, dose, geographic location of treatment, facility type, and distance from treatment facility. RESULTS: A total of 2,684 patients received GKRS, while 1,643 patients received LINAC SRS. After adjusting for significant covariates, treatment at non-academic facilities was associated with increased LINAC SRS receipt, most prominently in the Midwestern (OR=6.23;p<0.001), Northeastern (OR=4.42;p<0.001), and Southern US (OR=1.96;p<0.001). Compared to patients receiving 12-17 Gy, patients receiving doses of 18-19 Gy (OR=1.42;p=0.025), 20-21 Gy (OR=1.82;p<0.001), and 22-24 Gy (OR=3.11;p<0.001) were more likely to receive LINAC SRS; similarly, patients located within 20 miles of a radiation treatment facility were more likely to receive LINAC SRS (OR=1.27;p=0.007). CONCLUSIONS: Despite Gamma Knife being more prominently used over LINAC for SRS, patients treated at a non-academic facility outside of the Western US or requiring increased radiation dose were substantially more likely to receive LINAC over Gamma Knife. Additionally, patients residing in close proximity to a treatment center were 27% more likely to receive LINAC, likely indicative of the increased geographic accessibility of LINAC compared with GKRS.